2011
DOI: 10.1021/jp200297z
|View full text |Cite
|
Sign up to set email alerts
|

On the Relaxation Mechanisms of 6-Azauracil

Abstract: The nonadiabatic photochemistry of 6-azauracil has been studied by means of the CASPT2//CASSCF protocol and double-ζ plus polarization ANO basis sets. Minimum energy states, transition states, minimum energy paths, and surface intersections have been computed in order to obtain an accurate description of several potential energy hypersurfaces. It is concluded that, after absorption of ultraviolet radiation (248 nm), two main relaxation mechanisms may occur, via which the lowest (3)(ππ*) state can be populated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
76
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 53 publications
4
76
1
Order By: Relevance
“…The increase in the Scheme 6 Proposed relaxation mechanisms of 6-azauracil depicting the multiple pathways that lead to the T 1 (ππ*) state. Reprinted with permission from [25]. Copyright 2011 American Chemical Society internal conversion rate from the S 1 (nπ*) state to the ground state caused by intramolecular vibrational energy relaxation in 6-azauridine vs 6-azauracil [15] is in agreement with the relaxation model proposed by West et al [193], but in contrast to that by Hare et al [140,159].…”
Section: Excited-state Deactivation Mechanism In the Azabase Derivativessupporting
confidence: 86%
See 4 more Smart Citations
“…The increase in the Scheme 6 Proposed relaxation mechanisms of 6-azauracil depicting the multiple pathways that lead to the T 1 (ππ*) state. Reprinted with permission from [25]. Copyright 2011 American Chemical Society internal conversion rate from the S 1 (nπ*) state to the ground state caused by intramolecular vibrational energy relaxation in 6-azauridine vs 6-azauracil [15] is in agreement with the relaxation model proposed by West et al [193], but in contrast to that by Hare et al [140,159].…”
Section: Excited-state Deactivation Mechanism In the Azabase Derivativessupporting
confidence: 86%
“…The high triplet yield provides strong evidence that intersystem crossing to the triplet state is the primary Excited at 308 nm i The intersystem crossing lifetime was estimated to be <1 ps and a self-quenching rate constant of (6.6 AE 0.8) Â 10 8 M À1 s À1 was measured relaxation pathway in 6-azauracil and 6-azauridine, whereas internal conversion to the ground state, from either the S 1 (nπ*) or S 2 (ππ*) states, is inefficient. Calculations performed by the groups of Marian [20] and Borin [25] at the DFT/ MRCI/COSMO/cc-pVDZ and CASPT2//CASSCF/ANO-L levels of theory, respectively, support the above mechanism. Etinski and Marian [20] concluded that the S 1 (nπ*) state acts as a doorway state in the population of the T 1 (ππ*) state, where the S 2 (ππ*) state population is transferred nearly quantitatively to the S 1 (nπ*) state.…”
Section: Excited-state Deactivation Mechanism In the Azabase Derivativesmentioning
confidence: 72%
See 3 more Smart Citations